Royal Victoria Hotel Industrial Strategies and Efforts Towards the Impact of The Covid-19 Pandemic - Nidya Mery Larasanti; Dito Aditia Darma Nasution (Future Science, 2022)
The spread of the COVID-19 Virus occurred very quickly, the lack of responsive public awareness caused the virus to spread and eventually claimed lives and caused unrest. The COVID-19 pandemic has also affected economic activity. The impact of COVID-19 on the hospitality industry in Indonesia has also been badly affected. Various strategies were carried out by the hotel industry and the government in reducing the impact of increasingly large losses. The research aims to analyze the strategies and efforts of the Hotel Victoria industry towards the impact of the COVID-19 pandemic. A qualitative descriptive approach is the foundation of research by collecting data through observation, interviews and document studies. The conclusions from this research are; The occupancy rate of the Hotel Royal Victoria has fallen sharply. In 2019 the occupancy rate of Hotel Royal Victoria was 37%. The impact of the COVID-19 Pandemic includes decreasing hotel occupancy rates, increasing operational costs, and termination of employment. The strategies implemented by Hotel Royal Victoria in dealing with the COVID-19 pandemic include: having a CHSE certificate, issuing frugal Meals Box and Rice Bowl packages, promoting on social media, offering room rates with a 50% discount on travel platforms, and conducting employee reviews. whose contract has expired. These strategies were recognized as very effective and helped Hotel Royal Victoria survive during the COVID-19 pandemic.